Regulation of ciliary function by fibroblast growth factor signaling identifies FGFR3-related disorders achondroplasia and thanatophoric dysplasia as ciliopathies. (17th January 2018) - Kunova Bosakova, Michaela; Varecha, Miroslav; Hampl, Marek; Duran, Ivan; Nita, Alexandru; Buchtova, Marcela; Dosedelova, Hana; Machat, Radek; Xie, Yangli; Ni, Zhenhong; Martin, Jorge H; Chen, Lin; et al.
Abstract: Cilia project from almost every cell integrating extracellular cues with signaling pathways. Constitutive activation of FGFR3 signaling produces the skeletal disorders achondroplasia (ACH) and thanatophoric dysplasia (TD), but many of the molecular mechanisms underlying these phenotypes remain unresolved. Here, we report in vivo evidence for significantly shortened primary cilia in ACH and TD cartilage growth plates. Using in vivo and in vitro methodologies, our data demonstrate that transient versus sustained activation of FGF signaling correlated with different cilia consequences. Transient FGF pathway activation elongated cilia, while sustained activity shortened cilia. FGF signaling extended primary cilia via ERK MAP kinase and mTORC2 signaling, but not through mTORC1. Employing a GFP-tagged IFT20 construct to measure intraflagellar (IFT) speed in cilia, we showed that FGF signaling affected IFT velocities, as well as modulating cilia-based Hedgehog signaling. Our data integrate primary cilia into canonical FGF signal transduction and uncover a FGF-cilia pathway that needs consideration when elucidating the mechanisms of physiological and pathological FGFR function, or in the development of FGFR therapeutics.